The Padashon Demban Tradition of 'Delivering Betel' in the Batak Simalungun Community: A Study of Local Wisdom - Roma Hotni Uhur Purba; Tioara Monika Simarmata; Ridho Wahyu Cristian Silaban; Andreas Alessandro Hutagalung; Tomson Sibarani (Raja Zulkarnain Education Foundation, 2025)
This study examines the Padashon Demban tradition, also known as the tradition of giving betel to the Batak Simalungun people. This tradition is a cultural heritage that still lives on today. This study aims to identify the symbolic meaning, social function, and cultural values contained in the practice of giving betel as part of the Simalungun community’s way of life. This study employed a qualitative methodology and a descriptive approach. Data were collected through observation, interviews with traditional leaders and community members, and through literature research on various written sources on Simalungun traditions and culture. The study shows that Padashon Demban has various presentation forms, including Batu ni Demban, Demban Tugah-Tugah, Demban Tasakan, and Demban Gunringan. Each form has a unique purpose and meaning. This tradition embodies social, ethical, aesthetic, and spiritual values that emphasize the importance of respect, politeness, balance, and togetherness in community life. Betel is a symbol of goodwill, appreciation, and a way to strengthen social relationships and resolve problems peacefully. The Padashon Demban tradition demonstrates the strong cultural and moral values of the Batak Simalungun people. It is crucial to preserve this tradition so that future generations can recognize and practice the noble values that shape social harmony and the nation’s cultural identity.